'An ant against an elephant': Retirement village residents' experiences of disputes and dispute resolution. (3rd April 2018) - Malta, Sue; Williams, Susan B; Batchelor, Frances A
Abstract : Objective: To record Victorian retirement village residents' experiences of dispute management and satisfaction levels related to dispute resolution processes. Methods: Survey distributed to 6500 retirement village residents. Results: Surveys returned from 1876 residents (29% return rate). Most residents rated life in retirement villages as positive (mean 7.9/10), with an association between life satisfaction and management's ability to resolve disputes ( r s = 0.44, P < 0.01). Almost 70% of respondents reported issues of concern to management were resolved satisfactorily; 38% were not resolved to residents' satisfaction. One‐fifth reported contacting regional managers or higher personnel regarding issues affecting them, with two‐thirds of these respondents reporting a negative outcome. Over 30% did not know if their village had dispute resolution processes in place. Conclusion: Despite finding retirement village life positive, residents of retirement villages found disputes and dispute resolution processes unsatisfactory and desired change to address these concerns.